Insight into Informant Discrepancies Regarding Psychosexual Functioning of Adolescents with and without Autism Spectrum Disorder. (4th December 2019) - Dekker, Linda P.; Visser, Kirsten; van der Vegt, Esther J.M.; Maras, Athanasios; van der Ende, Jan; Tick, Nouchka T.; Verhulst, Frank C.; Greaves‐Lord, Kirstin
Abstract : The private nature of psychosexual functioning leads adolescents and their parents to have different perspectives, which highlights studying parent–child informant discrepancies in this domain. We investigated informant discrepancy in psychosexual functioning, using the self‐report and parent report versions of the Teen Transition Inventory (TTI), of adolescents with autism spectrum disorder (ASD; 136 parent–child dyads) compared to adolescents from the general population (GP; 70 parent–child dyads). Significantly larger informant discrepancies exist in ASD dyads than GP dyads in most domains of psychosexual functioning, except for Body image, Sexual behavior, and Confidence in the future. It is important to use and pay attention to both informants, as discrepancies are relevant for both research and clinical practice regarding psychosexual functioning.